Perancangan Aplikasi Pemesanan Material Furnishing Berbasis Android Di Arcade Living BSD City - Khoerun Nisa; Joko Riyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Ordering material is an activity that customers carry out to buy. To achieve customer satisfaction the company must have a good ordering system. The ordering system currently provided is to record the material requirements needed and then provide the notes to the admin. The research method used is by observing direct objects in existing problems as well as literature studies from various sources by searching for data. The resulting information system in the form of Android can solve problems in Arcade Living in managing furnishing material ordering data so that the data process becomes systematic and computerized. This android-based furnishing material ordering application at Arcade Living uses the Waterfall development method and the system implementation uses the Java and MySQL programming languages as a database and the system testing used uses black box testing.